KARAKTERISTIK KARAKTERISTIK HABITAT TAPIR ASIA (Tapirus indicus) DI KAWASAN SPTN I TAMAN NASIONAL TESSO NILO - SHIDDIEQY, MUHAMMAD AZIZ (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
Tapir Asia ( Tapirus indicus) is a plant-eating herbivorous animal (Goltenboth et al., 2012). Habitats that are suitable for survival, such as the availability of sufficient food and an environment that supports tapirs for breeding and resting which occupy places of life in the form of swamp habitats, lowlands, mountains, hill forests, secondary forests, dense shrubs and palm plantations (Ministry of Forestry, 2013). Tesso Nilo National Park is one of the natural forest areas that still provides a habitat for the continued preservation and rescue of rare animals, including the tapir. This study aims to determine the habitat characteristics of the Asian tapir (Tapirus indicus) in the SPTN I area of Tesso Nilo National Park. Determination of the position of the Asian tapir can be known by collecting data using direct and indirect observation methods. The habitat studied was selected using a purposive sampling technique, namely by exploring locations that are home ranges for tapirs. Observations were made using 1 transect line in each different habitat type. There are a total of 2 transect lines, there are 25 observation plots in each line so that a total of 50 observation plots. Habitat characteristics suitable for tapirs based on tree crown cover were 1.77% -14.14% shrubs and secondary forest tree canopy cover 17.68% -99.79%. Habitat characteristics for tapirs based on the availability of forage plant species are mostly found in shrub vegetation, 27.272% -96.55%. Based on the slope factor, the slope is at a level of 1% -21%, this is included in the flat and sloping category, then based on the altitude it ranges from 42.01 masl to 71.96 masl. The distance between secondary forest vegetation and natural forest is 810.89 m-1,220.43 m and the distance between shrub vegetation is 2,537.39 m-3,084.49 m and the distance from the river to secondary forest vegetation is 8.98 m-317.41 m and scrub vegetation 24.52 m-398.75 m.